Vancomycin-associated acute kidney injury epidemiology in children: a systematic review. Issue 10 (24th February 2022) - Williams, Chloe; Hankinson, Charlotte; McWilliam, Stephen J; Oni, Louise
Abstract : Introduction: Vancomycin is a recognised cause of drug-induced acute kidney injury (AKI). Objective: The aim of this systematic review was to summarise the incidence of, and the risk factors for, vancomycin-associated AKI (v-AKI) in children. Design: A systematic search was performed in November 2020 on the search engines PubMed, Web of Science and Medline, using predefined search terms. The inclusion criteria were primary paediatric studies, intervention with vancomycin and studies that included AKI as an outcome. Study quality was assessed using the relevant Critical Appraisal Skills Programme checklist. The data are reported using descriptive statistics. Results: 890 studies were identified and screened with 25 studies suitable for inclusion. A cohort of 12 730 patients with v-AKI were included and the incidence of v-AKI in children was found to be 11.8% (1.6%–27.2%). The median age of the cohort was 2.5 years (range 0–23) and 57% were male patients. Risk factors that increased the likelihood of v-AKI were concomitant use of nephrotoxic medications, increased trough concentrations and, to a lesser extent, increased dose, longer duration of treatment, impaired renal function and if the patient required paediatric intensive care. Conclusions: The incidence of v-AKI in children is significant and methods to reduce this risk should be considered. Further prospective interventional studies to understand the mechanisms of nephrotoxicity from vancomycin are needed and targeting risk factors may make vancomycin administration safer. Abstract : This systematic review concludes that the incidence of vancomycin-induced nephrotoxicity in children is relevant (11.8 %), so that caution during its use is warranted.